The Role of Debt Literacy in Shaping Loan Repayment Behavior in P2P Lending - Arya Putri, Annisa Maharani; Wijayanti, Risna; Champaca, Mychelia (FIA UB, 2026)
The rapid proliferation of peer-to-peer (P2P) lending in Indonesia has increased financial inclusion to 85.1% in 2022, with national literacy rising from 38.03% in 2019 to 49.68%. Nevertheless, non-performing loans (NPL) averaged 2.90% in 2023, primarily linked to younger borrowers from Generation Z, underscoring a paradox between greater accessibility/literacy and persistent repayment difficulties. This investigation addresses a pivotal research gap by positing that general financial literacy is insufficient to ensure credit adherence, underscoring the need for specialized debt literacy, which remains inadequately explored. The issue underscores how readily accessible credit amplifies impulsive behavior among Generation Z, driving consumer loans for technological devices and lifestyle expenditures. This study uses structural equation modelling with partial least squares (SEM-PLS) on quantitative data from 300 Generation Z P2P borrowers in East Java, Indonesia, to investigate whether debt literacy positively influences loan repayment behavior and to assess the mediating roles of overspending and money management skills. The findings demonstrate that debt literacy positively affects repayment behavior, with overspending and money management skills acting as significant partial mediators that reflect positive and negative behavioral pathways, respectively.